The evaluation of anaerobic co-digestion and ethanol fermentation for bioenergy production from 200 ha farmland in the UK. (3rd October 2016) - Guk, Erdogan; Kalkan, Naci
Abstract : Purpose: Bioenergy as a renewable energy type is found as a promising method to replace non-renewable energy. Anaerobic co-digestion, in which the microorganisms of two or more substrates break into biodegradable materials without oxygen, and fermentation, in which substances break into a simpler form in the presence of microorganisms and some bacteria, are the two frequently used methods that are were applied in this work. Design/methodology/approach: A farmland currently being used for farming was selected, and the bioenergy potential of the farmland was evaluated by using the aforementioned two methods. In this work, segregated municipal wastes which were collected from nearby areas and animal manure were used as feedstock for anaerobic co-digestion, whereas wheat straw obtained from the farmland was used as feedstock for fermentation. Findings: The total input energy required for the digestion systems and the collection of the feedstock products from the growth to the harvest phases was calculated. Thereafter, the generated output energy was calculated to obtain an energy balance of the techniques. All the processes were taken into account during the prediction of the cost of the given power plant. The power output capacity of the farmland was 245 MW with a total cost of $540, 200. Research limitations/implications: Because of the chosen research approach, the research results may lack generalisability. Therefore, researchers are encouraged to test the proposed propositions further. Originality/value: The result proves that the two methods were applicable and feasible to replace for the 200 ha farmland.